Modern Commerce Terms Semantic Functions (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is dedicated to the study of terminology at the international level, in addition to providing detailed information about the linguistic field to the scientific community, it describes the evolution of commercial terminology, the progress made to date and was aimed at exploring problematic debates. An important aspect of commercial terminology is that the evolution of terminologies often reflects their origins and traditional expressions. Business terminology refers to a complex set of terms and phrases needed to understand common practices in various areas of business operations and trade. Sales professionals need a deep understanding of specialized terminology to succeed in their field. The article covers the history and evolution of commercial terminology in science as a field of international economics and linguistics based on research by leading linguists and the national and cultural characteristics of the terms.